2011
DOI: 10.1007/s00380-011-0197-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erythropoietin on angiogenesis after myocardial infarction in porcine

Abstract: Erythropoietin (EPO) has recently been shown to confer cardioprotective effects via angiogenesis and antiapoptosis. The administration of EPO after myocardial infarction (MI) reduces infarct size and improves cardiac function in small animals. The purpose of this study is to investigate the protective effects of EPO in porcine MI. Each animal in the EPO group received four injections of recombinant human EPO (rhEPO; 6000 U per injection) at 2-day intervals, starting after coronary occlusion. Animals in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…[6] In addition, the PI3K/Akt signaling also mediates angiogenesis and VEGF expression in the ECs. [789] Wang et al . [10] found that the rh-EPO increased the mobilization of endothelial progenitor cells (EPCs) and subsequent promotion of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In addition, the PI3K/Akt signaling also mediates angiogenesis and VEGF expression in the ECs. [789] Wang et al . [10] found that the rh-EPO increased the mobilization of endothelial progenitor cells (EPCs) and subsequent promotion of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Erythropoietin has recently been shown to confer cardioprotective effects via angiogenesis and antiapoptosis in porcine myocardial injury [11]. Sulfur dioxide can decrease the activated ERS in rats with myocardial injury [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study systemic absorption was limited, as EPO was contained at the defect site—because of the almost avascular nature of the calvaria, and because of the fact that bone defects were sealed with bone wax (Wiltfang et al 2002). These measures were taken because porcine EPO has 80% DNA sequence homology with human EPO, and several groups have reported hematopoietic and pleiotropic effects of human recombinant EPO in swine (Wen et al 1993, Kawachi et al 2012). We studied the effect of EPO compared to within-subject saline controls by performing pairwise comparisons within the collagen carrier group, the autograft group, and the PCL scaffold group, and no comparisons between the 3 different treatment modalities were performed.…”
Section: Discussionmentioning
confidence: 99%